2019
DOI: 10.1155/2019/4853046
|View full text |Cite
|
Sign up to set email alerts
|

Control Strategy and Experiments for Robot Assisted Craniomaxillofacial Surgery System

Abstract: Since the intricate anatomical structure of the craniomaxillofacial region and the limitation of surgical field and instrument, the current surgery is extremely of high risk and difficult to implement. The puncturing operations for biopsy, ablation, and brachytherapy have become vital method for disease diagnosis and treatment. Therefore, a craniomaxillofacial surgery robot system was developed to achieve accurate positioning of the puncture needle and automatic surgical operation. Master-salve control and "ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Then, the system recognized teeth restoration materials with 5% of error. In [25], Tengfei Cui et al, demonstrated experiments for analyzing the robot assisted based craniomaxillo facial surgery process. The effective robot assisted system was developed to predict the exact position to inject the needle while doing surgical operations.…”
Section: Related Workmentioning
confidence: 99%
“…Then, the system recognized teeth restoration materials with 5% of error. In [25], Tengfei Cui et al, demonstrated experiments for analyzing the robot assisted based craniomaxillo facial surgery process. The effective robot assisted system was developed to predict the exact position to inject the needle while doing surgical operations.…”
Section: Related Workmentioning
confidence: 99%